COOPERATIVE OF TEAM GAMES TOURNAMENT TO ENHANCE LEARNING OUTCOMES IN ENGLISH LEARNING - Faidah Yusuf; Hikmawati Usman; Muhammad Irfan; Latri Aras; Hardianto Rahman (Journey: Journal of English Language and Pedagogy, 2023)
The challenge of teaching English to students with low academic achievement is what inspired this line of inquiry. The purpose of this research was to provide an explanation of how the Team Games Tournament was implemented Elementary class in order to improve the English learning outcomes of the pupils. The type of action research that was conducted in the classroom for the purpose of this study was approached from a qualitative point of view. A total of 24 students took part in this research project, both as instructors and as research subjects. As means of collecting data for the purpose of this investigation, observation reports, learning progress examinations, and documentation were utilized. The findings of the research are that the implementation of the Team Games Tournament was generally carried out in an effective manner. Less teacher activity was recorded during Cycle I Meeting I, which sufficient category, however, more teacher activity was recorded during Meeting II, which rated as "good." Because of this, the student's results in learning English have increased. The implementation of the Team Games Tournament learning model in an educational of elementary school to improve the learning outcomes for students has been shown to be beneficial.